A Brief Review of Chronic Obstructive Pulmonary Disease - James C Hogg (Canadian Respiratory Journal)
A recent study, based on a combination of multidetector computed tomography scanning of an intact specimen with microcomputed tomography and histological analysis of lung tissue samples, reported that the number of terminal bronchioles were reduced from approximately 44,500/lung pair in control (donor) lungs to approximately 4800/lung pair in lungs donated by individuals with very severe (Global initiative for chronic Obstructive Lung Disease stage 4) chronic obstructive pulmonary disease (COPD) treated by lung transplantation. The present short review discusses the hypothesis that a rapid rate of terminal bronchiolar destruction causes the rapid decline in lung function leading to advanced COPD. With respect to why the terminal bronchioles are targeted for destruction, the postulated mechanisms of this destruction and the possibility that new treatments are able to either prevent or reverse the underlying cause of airway obstruction in COPD are addressed.